Modified bilateral medial thigh fasciocutaneous flap for perineoscrotal reconstruction following Fournier’s gangrene - Mohd Said, Mohd Tarmizi; Yap, Pauline; Omar, Farah Hany; Mat Zain, Mohamad Ali; Shen, Tan Zhun (Wolters Kluwer Medknow Publications, 2026)
A 62-year-old man presented with Fournier’s gangrene following neglected scrotal hematoma, resulting in a large perineum defect. Traditional reconstruction methods such as skin grafts often result in limited durability and protection. To address these shortcomings, we adapted and refined Hirschowitz’s thigh flap technique with two critical modifications: a rotation-advancement movement and secondary defect closure using posterior thigh triangular transposition flaps arranged in Z-plasty fashion. This approach addressed the dual challenges of donor-site tension and defect coverage in this complex perineoscrotal reconstruction. The modified flaps achieved complete sensate scrotal coverage with viable tissue, requiring only conservative management for minor edge breakdown. By postoperative week 3, the patient regained normal voiding function with excellent esthetic contour and no midline complications. Our technique builds on the reliable vascularity of medial thigh flaps which are the deep external pudendal artery, superficial femoral artery, and medial circumflex femoral artery pedicles while solving the tension limitations of primary closure, particularly valuable for patients who have completed family, nondiabetic, and nonsmoker. This option of perineoscrotal reconstruction offers a pragmatic single-stage solution that balances functional restoration and esthetic outcomes better than skin graft.